High‐Mannose Oligosaccharide Hemimimetics that Recapitulate the Conformation and Binding Mode to Concanavalin A, DC‐SIGN and Langerin - Herrera‐González, Irene; González‐Cuesta, Manuel; Thépaut, Michel; Laigre, Eugénie; Goyard, David; Rojo, Javier; García Fernández, José M.; Fieschi, Franck; Renaudet, Olivier; Nieto, Pedro M.; Ortiz Mellet, Carmen (Chemistry : a European journal, 2024)
The “carbohydrate chemical mimicry” exhibited by sp2‐iminosugars has been utilized to develop practical syntheses for analogs of the branched high‐mannose‐type oligosaccharides (HMOs) Man3 and Man5. In these compounds, the terminal nonreducing Man residues have been substituted with 5,6‐oxomethylidenemannonojirimycin (OMJ) motifs. The resulting oligomannoside hemimimetic accurately reproduce the structure, configuration, and conformational behavior of the original mannooligosaccharides, as confirmed by NMR and computational techniques. Binding studies with mannose binding lectins, including concanavalin A, DC‐SIGN, and langerin, by enzyme‐linked lectin assay and surface plasmon resonance revealed significant variations in their ability to accommodate the OMJ unit in the mannose binding site. Intriguingly, OMJMan segments demonstrated “in line” heteromultivalent effects during binding to the three lectins. Similar to the mannobiose (Man2) branches in HMOs, the binding modes involving the external or internal monosaccharide unit at the carbohydrate binding‐domain exist in equilibrium, facilitating sliding and recapture processes. This equilibrium, which influences the multivalent binding of HMOs, can be finely modulated upon incorporation of the OMJ sp2‐iminosugar caps. As a proof of concept, the affinity and selectivity towards DC‐SIGN and langerin were adjustable by presenting the OMJMan epitope in platforms with diverse architectures and valencies. The “carbohydrate chemical mimicry” of sp2‐iminosugars enables the synthesis of high‐mannose‐type oligosaccharide analogs whose solution and lectin bound conformations match those of the natural partners. Upon multivalent presentation, enhanced affinities towards ConA, DC‐SIGN and langerin are achieved, with distinct selectivity profiles.